Communication for behavioural impact in enhancing utilization of insecticide-treated bed nets among mothers of under-five children in rural North Sudan: an experimental study - Elmosaad, Yousif Mohammed; Elhadi, Magda; Khan, Asif; Malik, Elfatih Mohamed; Mahmud, Ilias (© 2016 BioMed Central Ltd., 2018)
This article was published in the Malaria Journal [ © 2016 The Author(s).] and the definitive version is available at: http://doi.org/10.1186/s12936-016-1551-8 The Journal's website is at: https://malariajournal.biomedcentral.com/articles/10.1186/s12936-016-1551-8